DETERMINASI VARIABEL AKUNTANSI TERHADAP PENENTUAN KEBIJAKAN STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Indra Saputra; Farah Margaretha (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2015)
Decisions incompliance with the company's funds come fromits own capital (equity) or by foreign capital (debt). The purpose of this study was to determine the effect of firm size, profitability, business risk, asset structure, cash holdings, non-debt tax shield, signaling and growth effects of capital structure policy. This research was conducted on37samples of companies listed on the Indonesia Stock Exchange(IDX) using time series data from 2008-2011. This study uses multiple linear regression to test the hypothesis to see the contribution of each variable individually and simultaneously in influencing the structure of funding. The results show that firm size, asset structure, and signaling effect has a positive and significant effect on the capital structure policy. Other variables, namely business risk and cash holdings have a negative correlation and significant effect on the capital structure of these results support the trade of theory and pecking order theory. Further testing of profitability, non-debt tax shield and the growth does not affect the capital structure in manufacturing companies. If the company uses debt funding source soft he factors accounting variables such as firm size, asset structure, business risk and the effect of signaling a decisive factor in the decision making of the company's capital structure policy so as to provide optimal results.